2004
DOI: 10.1081/prg-120028281
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Preeclampsia and Oxygen Environment on Endothelial Release of Matrix Metalloproteinase‐2

Abstract: Preeclamptic endothelial cells demonstrate significantly enhanced MMP-2, TIMP-1 and TIMP-2 release compared to normal cells. Our data show that there are significant effects of oxygen tension on MMP-2 release from normal cells; however, the magnitude of the enhanced release is small when compared to the differences in MMP-2 release in cells from preeclamptic and normal pregnancies. Furthermore, TIMP-1 and -2 release is not affected by changes in oxygen. It is unlikely that oxygen is a key mediator of the enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 52 publications
3
21
0
Order By: Relevance
“…The observed high expression of MMP2 in maternal blood in preeclampsia is consistent with the documented high level of MMP2 in preeclamptic plasma (Myers et al 2005) and might have a role in regulating vascular tone, as highlighted by a recent study that suggested the role of MMP1 expression in vasoconstriction (Mousa et al 2012). Consistent with our results, high levels of TIMP1 and TIMP2 have been demonstrated in preeclamptic endothelial cells (Merchant et al 2004). High expression levels of TIMP2 and TIMP1 in preeclampsia might be further decreasing the activities of already compromised levels of MMP2 and MMP1, respectively, hence leading to decreased invasion of uterine vasculature.…”
Section: Discussionsupporting
confidence: 80%
“…The observed high expression of MMP2 in maternal blood in preeclampsia is consistent with the documented high level of MMP2 in preeclamptic plasma (Myers et al 2005) and might have a role in regulating vascular tone, as highlighted by a recent study that suggested the role of MMP1 expression in vasoconstriction (Mousa et al 2012). Consistent with our results, high levels of TIMP1 and TIMP2 have been demonstrated in preeclamptic endothelial cells (Merchant et al 2004). High expression levels of TIMP2 and TIMP1 in preeclampsia might be further decreasing the activities of already compromised levels of MMP2 and MMP1, respectively, hence leading to decreased invasion of uterine vasculature.…”
Section: Discussionsupporting
confidence: 80%
“…The endothelial nature of these cells was confirmed by staining for the endothelium-specific marker, von Willebrand’s factor (data not shown). Our laboratory has published extensively using HUVECs as a model for the vascular endothelium [40,41,42,43,44]. …”
Section: Methodsmentioning
confidence: 99%
“…Studies suggest that plasma levels of MMP-2, MMP-9, TIMP-1, and TIMP-2 are higher in HTN-Preg than Norm-Preg women (Merchant et al2004; Tayebjee et al2004). Other studies have shown that the levels of MMP-2 and -9 in decidua cells are not elevated in PE (Huisman et al, 2004).…”
Section: Introductionmentioning
confidence: 99%